PELATIHAN STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN KINERJA ANGGOTA UMKM CIBODAS JASA DI KECAMATAN CIBODAS - Mila Amri; Rayhan Nugraha; Tia Najwa Harvia Shinta; Sephia Yetta Annisa (Universitas Mataram, 2026)
Cibodas Jasa MSMEs are a collaboration forum or MSME Outlets in Cibodas District, Tangerang City. One of the main problems of Cibodas Jasa MSMEs is the lack of digital marketing skills with 93% not having Google Maps, WA Business, TikTok Shop, Tokopedia, and Shopee accounts (n=15 participants). This service initiative aims to improve digital capabilities through intensive training in 4 stages. The implementation uses the lecture-demonstration-practice-review method with a mentoring ratio of 1:4 for 8 hours at the Cibodas Jasa MSME Outlet. The results showed a 100% transformation (75 active accounts from 0), visible observation confirmed all participants were ready to sell online tomorrow morning. The establishment of the Cibodas Jasa Digital WA group ensures the sustainability of the 6-month program with the target of replication to other RTs. The direct practice approach is effective in empowering MSME housewives independently.